Phase IIb dose-ranging study of the oral JAK inhibitor tofacitinib (CP-690,550) or adalimumab monotherapy versus placebo in patients with active rheumatoid arthritis with an inadequate response to disease-modifying antirheumatic drugs - Fleischmann, Roy; Cutolo, Maurizio; Genovese, Mark C.; Lee, Eun Bong; Kanik, Keith S.; Sadis, Seth; Connell, Carol A.; Gruben, David; Krishnaswami, Sriram; Wallenstein, Gene; Wilkinson, Bethanie E.; Zwillich, Samuel H. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To compare the efficacy, safety, and tolerability of 5 doses of oral tofacitinib (CP‐690,550) or adalimumab monotherapy with placebo for the treatment of active rheumatoid arthritis (RA) in patients with an inadequate response to disease‐modifying antirheumatic drugs. Methods In this 24‐week, double‐blind, phase IIb study, patients with RA (n = 384) were randomized to receive placebo, tofacitinib at 1, 3, 5, 10, or 15 mg administered orally twice a day, or adalimumab at 40 mg injected subcutaneously every 2 weeks (total of 6 injections) followed by oral tofacitinib at 5 mg twice a day for 12 weeks. The primary end point was the responder rate according to the American College of Rheumatology 20% improvement criteria (ACR20) at week 12. Results Treatment with tofacitinib at a dose of ≥3 mg twice a day resulted in a rapid response with significant efficacy when compared to placebo, as indicated by the primary end point (ACR20 response at week 12), achieved in 39.2% (3 mg; P ≤ 0.05), 59.2% (5 mg; P < 0.0001), 70.5% (10 mg; P < 0.0001), and 71.9% (15 mg; P < 0.0001) in the tofacitinib group and 35.9% of patients in the adalimumab group (P = 0.105), compared with 22.0% of patients receiving placebo. Improvements were sustained at week 24, according to the ACR20, ACR50, and ACR70 response rates as well as classifications of remission according to the 3‐variable Disease Activity Score in 28 joints (DAS28) using C‐reactive protein and the 4‐variable DAS28 using the erythrocyte sedimentation rate. The most common treatment‐emergent adverse events (AEs) in patients across all tofacitinib treatment arms (n = 272) were urinary tract infection (7.7%), diarrhea (4.8%), headache (4.8%), and bronchitis (4.8%). Conclusion Tofacitinib monotherapy at ≥3 mg twice a day was efficacious in the treatment of patients with active RA over 24 weeks and demonstrated a manageable safety profile.